CONSTITUTIONAL AND LEGAL FOUNDATIONS OF THE RIGHT TO USE QUALIFIED MEDICAL SERVICES IN THE REPUBLIC OF UZBEKISTAN - Komilova Muxtasar Abdunabi qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article highlights the importance of citizens' health, reforms carried out by the head of state in this regard, attention and care given to minors, powers of the Cabinet of Ministers in the field of health care.